Biologische Variablen in sozialwissenschaftlichen Surveys - Rainer Schnell (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
– Social scientists have ignored biological constraints of human behavior for a long time almost completely. If prediction of behavior is considered as essential for a social science. The neglect of any variable, which might influence human behavior, is hardly justified. Therefore, this paper gives examples of such biological variables and their measurement in social surveys.
Keywords: C81; D03; Y8; 330; bio-social surveys; behavioral genetics; biobanks; sociobiology